Coronary Artery Perforation following Percutaneous Coronary Intervention in an Elderly Patient: A case report - Barua, Sumit; Hasan, Md Kamrul; Raha, Sanjay Kumar; Rahaman, Md Salahuddin; Hossain, Md Sorower (Bangladesh Medical Journal, 2023)
Percutaneous coronary intervention (PCI) is widely used in the diagnosis and treatment of symptomatic coronary artery disease. However, much like any other procedure, it has its risks; one such rare but lethal complication is coronary artery perforation (CAP) which requires immediate intervention. Prompt recognition and appropriate treatment strategy are of utmost importance in reducing the mortality and morbidity. We herein report a case of Ellis Type III perforation of the left anterior descending coronary artery (LAD) during PCI who underwent emergency coronary artery bypass grafting (CABG) refractory to conventional coronary stent placement and balloon tamponade. The patient recovered well despite excessive initial postoperative bleeding and was discharged from the hospital. Bangladesh Med J. 2022 May; 51(2): 54-58